Perbedaan Motivasi dan Hasil Belajar Biologi Melalui Model Discovery Learning dengan Teknik Probing Prompting Peserta Didik Kelas XII SMAN 8 Luwu Utara - Kasman, Irmawati; Daud, Firdaus; Danial, Muhammad (UNM Journal of Biological Education, 2023)
This study is a quasi-experimental research (quasi-experimental design) which aims to examine the differences in motivation and learning outcomes of biology through the Discovery Learning model with Probing Prompting technique of grade XII students at SMAN 8 in North Luwu. The aims of the study are to analyze the difference in motivation and biology learning outcomes through the Discovery Learning model with Probing Prompting technique of grade XII students at SMAN 8 in North Luwu. The population in this study were students of grade XII MIPA at SMAN 8 in North Luwu in academic year of 2021/2022. Samples were taken by employing Random Sample technique. Learning motivation data were collected using a learning motivation questionnaire and learning outcomes were collected using multiple choice tests. Data were analyzed by employing descriptive analysis and inferential analysis. Data collection in this study used a questionnaire technique and a test technique. The results of hypothesis testing using the MANOVA (Multivariate Analysis of Variance) test of the significance value learning motivation sig (2-tailed) < ???? = 0.05 or 0.023 < ???? 0.05 means H0 is rejected and H1 is accepted and learning outcomes with sig (2-tailed) < ???? = 0.05 or 0.003 < ???? 0.05 means that H0 is rejected and H1 is accepted. Based on the test criteria, it can be concluded that there are differences in motivation and learning outcomes of biology through the Discovery Learning model with Probing Prompting technique of grade XII students at SMAN 8 in North Luwu.